Perceptions of land tenure security in pastoral areas in Marsabit, Kenya - Otieno, Ken; Lumumba, Odenda; Odote, Collins; Akinyi, Lydia; Wari, Gayo; Ongesa, Laureen; Nassef, Magda (2024)
These studies acknowledge the complexity of collective (communal) tenure in pastoral areas, which encompasses a multifaceted system of rights. It analyses two layers of tenure security: the security of the entire community and the security of individual members within that community, including differences related to gender and age. Additionally, the study explores the role of pastoral mobility in the context of tenure rights and pastoralism. This study examines two dimensions of tenure security: the security of the community as a whole and the security of individual members within that community, taking into account factors such as gender and age. In addition, we examined the role of mobility within a functional pastoral system. We found that the measurement of tenure security, including individual perceptions and perceived tenure security, is considerably more challenging in pastoral contexts compared to farming or settled households, where there are clear individual land titles for specific demarcated areas. Consequently, pastoral tenure and its varying degrees of security are not adequately captured in global measurement frameworks like Prindex, LANDex and other monitoring platforms contributing to the UN Sustainable Development Goals.